AODWE-007 Real world data on the effectiveness and safety of vedolizumab in the treatment of crohn's disease and ulcerative colitis: the edinburgh experience. (17th June 2017) - Plevris, N; Manship, TA; Deekae, A; Jones, GR; Noble, CL; Satsangi, J; Shand, AG; Arnott, ID; Lees, CW
Abstract : Introduction: The GEMINI clinical trials programme has demonstrated the efficacy and safety of vedolizumab in the induction and maintenance of Crohn's disease and ulcerative colitis. 2 years after licensing and subsequent approvals (eg. NICE/SMC), there is great interest in real world effectiveness and safety data from early adopters. Here, we present the short and medium term outcomes from a single centre cohort of IBD patients treated with vedolizumab. Method: The following were prospectively collected for all patients at each infusion: observations, routine haematology, biochemistry and inflammatory markers, clinical disease activity score, faecal calprotectin (FC) and adverse events. Clinical effectiveness was evaluated by assessing changes in HBI and SCCAI at 12–14 weeks and 26 weeks. Clinical remission was defined as a HBI <5 and SCCAI <3. Response was defined as a change in disease activity ≥3. Changes in CRP/FC were also analysed. Results: By the end of November 2016, 94 patients had received vedolizumab treatment. 63/94 (27 CD, 33 UC, 3 IBDU) had completed 12–14 week follow-up and are included in the primary analysis of clinical efficacy. Median disease duration was 7.9 years (IQR 4–15) with 36/63 (57%) patients previously exposed to anti-TNF therapy. Median HBI and SCCAI at baseline were 4 (IQR 2–7) and 5 (IQR 2–6) respectively. At 12–14 weeks median HBI was 3 (IQR 1–7) (p=0.37) with SCCAI dropping to 1 (IQR 1–3) (p=0.004). At 26 weeks median HBI fell to 2 (IQR 0.5–3, n=15) (p=0.02) and SCCAI remained at 1 (IQR 0–1, n=26) (p=0.0001). 23/63 (37%) patients were in clinical remission at baseline (59% on steroids) with 42/63 (67%) at 12–14 weeks (24% on steroids) and 35/41 (85%) at 26 weeks (12% on steroids). Clinical response and remission rates of those patients with clinically active disease at baseline were 61% and 53% at week 12–14 (n=36), and 78% for both at week 26 (n=24). Median FC was 730 µg/g (IQR 215–858, n=50) at baseline, 170 µg/g (IQR 60–465, n=36) at week 12–14 (p=0.00018) and 70 µg/g (IQR 30–180, n=29) at week 26 (p=0.00001). No significant drug related complications were observed. Arthralgia was the most commonly reported side effect (12/94). 7/94 (7%) patients underwent surgery within 30 weeks of starting vedolizumab. 2 pregnancies and 1 colorectal cancer were reported in our cohort. Conclusion: Our experience further supports the clinical effectiveness and safety data for the use of vedolizumab. We demonstrate a clear benefit in clinical/biochemical disease activity in a cohort of IBD patients many of which had complex and previously refractory disease. Disclosure of Interest: None Declared